ANALISIS UPAH MINGGUAN DALAM MENINGKATKAN KESEJAHTERAAN KARYAWAN DI SEKTOR UMKM - Maulana Syarif Afwa (Jurnal Ilmiah Ekonomi Syariah, 2026)
This study aims to analyze strategies for strengthening Islamic financial literacy among Generation Z through the implementation of gamification in financial technology (fintech) applications. The background of this research is based on the relatively low level of Islamic financial literacy among Generation Z, despite the significant increase in fintech usage. This study employs a qualitative approach with a descriptive-analytical method. Data collection techniques were conducted through a literature study by gathering journals, scientific articles, books, and documents published within the last ten years that are relevant as the basis for analysis. The findings indicate that the level of Islamic financial literacy among Generation Z remains moderate to low, with a gap between conceptual understanding and practical implementation. The use of fintech is predominantly influenced by convenience and efficiency rather than adherence to Islamic financial principles. Factors contributing to the low level of literacy include limited educational exposure, lack of Islamic financial content, and the dominance of conventional financial systems. Digital literacy plays a significant role in enhancing understanding of Islamic finance. Furthermore, the application of gamification in fintech demonstrates effectiveness in increasing user engagement and comprehension. Therefore, strengthening Islamic financial literacy through gamification can serve as an innovative approach that aligns with the characteristics of Generation Z in the digital era.